Burden of neurodegenerative diseases in the Eastern Mediterranean Region, 1990–2016: findings from the Global Burden of Disease Study 2016. (31st May 2019) - Fereshtehnejad, S.‐M.; Vosoughi, K.; Heydarpour, P.; Sepanlou, S. G.; Farzadfar, F.; Tehrani‐Banihashemi, A.; Malekzadeh, R.; Sahraian, M. A.; Vollset, S. E.; Naghavi, M.; Vos, T.; Feigin, V.; et al.
Abstract : Background and purpose: The Eastern Mediterranean Region (EMR) is experiencing a demographic shift towards rapid aging at a time of political unrest. We aimed to estimate the burden of neurodegenerative disorders and its relationship with sociodemographic index in the EMR countries from 1990 to 2016. Methods: Using data from the Global Burden of Disease Study 2016, we calculated country‐specific trends for prevalence, mortality, disability‐adjusted life‐years (DALY), years of life lost and years lived with disability (YLD) for Alzheimer's disease/other dementias and Parkinson's disease in the EMR during 1990–2016. Results: In the EMR, the age‐standardized prevalence rate of Alzheimer's disease/other dementias and Parkinson's disease was estimated at 759.8/100 000 (95% uncertainty intervals, 642.9–899.9) and 87.1/100 000 (95% uncertainty intervals, 69.8–108.2) people in 2016, demonstrating 0.01% and 42.3% change from 1990, respectively. Neurodegenerative disorders contributed to 5.4% of total DALY and 4.6% of total YLD among the older EMR population (70 years of age or older in 2016). Age‐standardized DALY due to Parkinson's disease were strongly correlated with the sociodemographic index level ( r  = 0.823, P  < 0.001). The YLD:DALY ratio of neurodegenerative diseases declined during this period in the low‐income but not the high‐income EMR countries. Conclusions: Our findings demonstrated an increasing trend in the burden of dementias and Parkinson's disease in most EMR countries between 1990 and 2016. With aging of the EMR populations, countries should target the modifiable risk factors of neurodegenerative diseases to control their increasing burden.